Reversible Conduction Failure in Anti-lactosylceramide-antibody-positive Combined Central and Peripheral Demyelination - Masaya Harada; Shiroh Miura; Hiroshi Kida; Taiga Moritaka; Ken-ichi Irie; Takashi Kamada; Yusuke Uchiyama; Sayuri Shima; Tatsuro Mutoh; Tomoaki Hoshino; Takayuki Taniwaki (Frontiers in Neurology, 2019)
We describe a 60-year-old woman with combined central and peripheral demyelination who presented with obstinate constipation, weakness in the lower limbs, and a bilateral sensory disturbance below her chest followed by girdle sensation in the right region of the abdomen, which was responsive to steroid therapy and plasmapheresis. Serum anti-lactosylceramide antibody was positive without anti-neurofascin 155 antibody or anti-galactocerebroside antibody positivity. Two months later, the patient had a first relapse that was responsive to steroid treatment. A nerve conduction study confirmed reversible conduction failure (RCF) in both episodes. Our case is unique in that she had an RCF episode as well as some similarities to encephalomyeloradiculoneuropathy.